The complete mitochondrial genome of Cyclina sinensis (Veneroida:Veneridae) - Dong, Pengzhi (Mitochondrial DNA B Resour, 2016)
Cyclina sinensis belongs to the family Veneroida, Veneridae, a marine mollusks having high economic value. It is distributed in the coastal waters of Southeast Asia. In recent years, the recourses of C. sinensis have been severely depleted due to overfishing and pollution. Genetic divergency has also been reported. It is necessary to protect this bivalve from the hazards. In this study, the complete mitochondrial genome of C. sinensis has been determined. The total number of nucleic acids were 21 799 bp. The genome contains 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and a non-coding control region. The phylogenetic analysis was conducted with 11 related species and confirmed the classification status.